Drug Repurposing on G Protein-Coupled Receptors Using a Computational Profiling Approach - de Felice, Alessandra; Aureli, Simone; Limongelli, Vittorio (Frontiers in Molecular Biosciences, 2021)
G protein-coupled receptors (GPCRs) are the largest human membrane receptor family regulating a wide range of cell signaling. For this reason, GPCRs are most wanted drug targets, with approximately 40% of prescribed medicines targeting one member of this receptor family. The structural homology of GPCRs and the broad spectrum of application of GPCR-acting drugs suggest to investigate cross-activity of a drug towards different GPCR receptors with the aim at rationalising drug side effects, designing more selective and less toxic compounds, and possibly proposing off-label therapeutic applications. Herein, we present an original in-silico approach named “Computational Profiling for GPCRs” (CPG), which is able to represent in 1D string the physico-chemical properties of a ligand/GPCR binding interaction and through a tailored alignment algorithm repurpose the ligand for a different GPCR. We show three case studies where docking calculations and pharmacological data confirm the drug repurposing findings obtained through CPG on 5-hydroxytryptamine receptor 2B, beta-2 adrenergic receptor and M2 muscarinic acetylcholine receptor. The CPG code is released as a user-friendly graphical user interface with numerous options that make CPG a powerful tool to assist drug design of GPCR ligands.